2013
DOI: 10.3109/13625187.2013.824564
|View full text |Cite
|
Sign up to set email alerts
|

Medical abortion: A path to safe, high-quality abortion care in Latin America and the Caribbean

Abstract: Despite highly restrictive abortion laws in LAC, MA increases access to safer abortion. Yet, significant barriers remain and much more must be done to enhance use of modern contraceptive and safer abortion methods among women in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Although we are unable to distinguish between arbitrarily induced or self-induced abortions and miscarriages in this study, the data support evidence from prior studies that some women in Ecuador are intentionally terminating their pregnancies despite the ban on abortions 21,23,34. Interestingly, during the analyses, we found that abortion rates had declined in 2014.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although we are unable to distinguish between arbitrarily induced or self-induced abortions and miscarriages in this study, the data support evidence from prior studies that some women in Ecuador are intentionally terminating their pregnancies despite the ban on abortions 21,23,34. Interestingly, during the analyses, we found that abortion rates had declined in 2014.…”
Section: Discussionsupporting
confidence: 76%
“…Due to the lack of data, the causes of differences in abortion ratios by province have not been studied yet; however, cultural, educational and better health care systems might be related to the higher number of abortions among the most populated provinces 34. When we compared the number of abortions with the number of children born each year, we observed that Pastaza, one of the least populated provinces with high cultural diversity, reported more abortions than any other provinces with numbers totaling 186/1,000 births.…”
Section: Discussionmentioning
confidence: 99%
“…Women have long known about misoprostol's abortifacient effect and used it on their own to end unwanted pregnancies, especially in Latin America, where it has been linked to a decline in abortion‐related morbidity and mortality from more harmful methods [14].…”
Section: What Can Obstetrician/gynecologists Do?mentioning
confidence: 99%
“…Liberalization of abortion laws could lead to major reductions in abortion‐related morbidity and mortality in Africa; however, such policy changes are slow to occur, suggesting that targeted interventions must be initiated during the interim period. A risk‐reduction approach to unsafe abortion—i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A risk‐reduction approach to unsafe abortion—i.e. harm reduction—has proven an effective strategy for reducing maternal deaths in Latin America and the Caribbean . Harm reduction involves the implementation of strategies that aim to reduce damage caused by behaviors that cannot easily be changed, especially in settings where such behaviors are driven underground by prohibitive and stigmatizing policies and practices .…”
Section: Introductionmentioning
confidence: 99%